New Waves in Metaphysics
X, 280 p.
Keywords: A collection of new essays by young scholars on the cutting edge of this ancient philosophical area. Diverse topics, including ontology, free will, fundamental properties, and causation, the volume will appeal both to specialists and to anyone interested in the present and future state of metaphysics in the English-speaking world.